Assessment of safe injection awareness and practices among healthcare providers at primary health care facilities - Lamia Ali; Randa Eldessouki (SpringerOpen, 2023)
Abstract Background Unsafe injection necessitates some preventive steps including promoting and assuring the execution of safe injection administration and waste disposal methods. The present study aimed to assess the awareness and practices of safe injection among health care providers working at all primary health care (PHC) facilities in Fayoum governorate, Egypt. Also, it assessed the awareness, readiness, and response related to needle stick injuries (NSIs). Methods A cross-sectional observational study conducted from September to December 2019 at all working PHC facilities in Fayoum Governorate, Egypt, resulted in enrolling 685 health care providers, and observation of 520 injection processes. Data were collected by a combination of staff interviews and structured observation of different injection processes using the WHO revised C tool. Results Safe injection and post-exposure NSI policies and procedures was implemented in 96.5% of the PHC facilities. Compliance to hand wash before preparing a procedure was 56.7%. Immediate disposal of used needles was 76.2% in observed injections. Hepatitis B vaccination rate among participants was 87.2%. Most participants 87.6% admitted the existence of a NSI reporting system but only 38.8% of those who had experienced NSI event reported. The rate of NSI was 14%. Conclusions Fayoum PHC facilities have good awareness level among providers and broadly accepted compliance with injection practices as per the WHO tool. Most injection-safety aspects were satisfactory, and implemented measures to face NSI were in place. Appropriate timely actions are required to maintain the fair awareness and improve injections practices in the PHC facilities.